1992
DOI: 10.1287/mnsc.38.10.1445
|View full text |Cite
|
Sign up to set email alerts
|

Top Team Deterioration as Part of the Downward Spiral of Large Corporate Bankruptcies

Abstract: This exploratory study of 57 large bankruptcies and 57 matched survivors examined the top management team (TMT) characteristics associated with major corporate failure. Prior research was used to guide selection of specific team characteristics for study. Not only did the failing firms show significant annual, or cross-sectional, divergence from survivors on several indicators of TMT composition, but also those divergences became more pronounced, even accelerating, over the last five years of the bankrupts' li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
431
1
10

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(463 citation statements)
references
References 37 publications
21
431
1
10
Order By: Relevance
“…Their research shows that past research has extensively investigated reputational issues affecting the reaction of financial markets to extraordinary events (e.g., D' Aveni and Kesner, 1993;Hambrick and D' Aveni, 1992;Schnietz and Epstein, 2005). Our research like-wise points to the role of reputation in special situations, and the applicability of qualitative corporate factors in capital markets.…”
Section: Conclusion and Future Researchsupporting
confidence: 57%
“…Their research shows that past research has extensively investigated reputational issues affecting the reaction of financial markets to extraordinary events (e.g., D' Aveni and Kesner, 1993;Hambrick and D' Aveni, 1992;Schnietz and Epstein, 2005). Our research like-wise points to the role of reputation in special situations, and the applicability of qualitative corporate factors in capital markets.…”
Section: Conclusion and Future Researchsupporting
confidence: 57%
“…Recent meta-analysis has found that the relationship between firm performance and board size is stronger for smaller, as compared to larger firms (Dalton et al 1999). Filatotchev and Toms (2003) and Hambrick and D'Aveni (1992) argue similarly that board diversity and director interlocks may play an important role in crisis situations, since, from a resourcedependency view, these board structures may generate more diverse networking opportunities to resource providers. Research on IPOs (Certo et al 2001;Filatotchev and Bishop 2002;Sanders and Boivie 2004) also demonstrates that board diversity supports wealth-creating aspects of corporate governance in newly listed companies.…”
Section: Contingenciesmentioning
confidence: 99%
“…This factor is also composed of prescriptive works such as contingency theory for turnaround (Hofer, 1980), hierarchy of change and structural growth (Katz & Kahn, 1966) and a chapter on competitive strategy in declining industries from Michael Porter's book (Porter, 1980). The first factor of the second period, covering 1991 to 2002, was TMT in organizational decline, made up of studies on the TMT in decline situations (Altman & Hotchkiss, 1983;Gilson, 1989) and especially in the case of bankruptcy, such as studies on TMT as a scapegoat (Boeker, 1992;, the deterioration of the TMT (Hambrick & D'Aveni, 1992;Moulton & Thomas, 1993), and the stigma of TMT (Sutton & Callahan, 1987). This factor also included studies on decision making in situations of risk (Singh, 1986), threat-rigidity effects (Staw et al, 1981) and the aforementioned resource dependence theory (Pfeffer & Salancick, 1978).…”
Section: -2014mentioning
confidence: 99%
“…The second factor, decline process includes the works that address the characteristics inherent to decline (D'Aveni 1989b; Hambrick & D'Aveni, 1988) and adaptation, decision making and TMT (Hambrick & D'Aveni, 1992;Meyer, 1982;Singh, 1986;Staw et al, 1981). The third factor is also called mortality.…”
Section: -2014mentioning
confidence: 99%